Modeling of machining parameters affecting flank wear and surface roughness in hot turning of Monel-400 using response surface methodology (RSM). (April 2019) - Kumar Parida, Asit; Maity, Kalipada
Highlights: Experimental investigation and modeling of flank wear and surface roughness in hot machining of Monel-400. Temperature and cutting speed was most affect parameters on flank wear and surface roughness. Error % between predicted and measured surface roughness and flank wear was 7 and 13 respectively. Abstract: In this study, the hot turning of Monel-400 has been performed to investigate the influence of four machining factors (cutting speed, feed rate, depth of cut and workpiece temperature) on flank wear and surface roughness. The workpiece has been heated with a mixture of oxygen and liquid petroleum gas. The experiments have been carried out based on face centered composite design (CCD). Response surface methodology (RSM) has been used to perform the mathematical modeling of flank wear and surface roughness. The influence of individual parameter on responses has been evaluated using ANOVA analysis. The predicted model for flank wear and surface roughness obtained from the regression equation shows good agreement with the experiment results. A maximum error of 13% and 7% of flank wear and surface roughness has been observed between the simulated and experimental results respectively.